Análise do efeito causal das restrições aos veículos de carga em cidade brasileiras - Paulo Henrique Fernandes Fonseca (2024)
Freight vehicle restrictions were measures widely adopted by Brazilian municipalities to minimize the effects of congestion, air pollution, and accidents. However, few studies have evaluated the effectiveness and impacts of such measures in the Brazilian context. In this sense, this project aims to analyze the causal effects of freight vehicle restrictions on the fleet (light freight vehicles and heavy freight vehicles) in the municipalities of the metropolitan regions of Belo Horizonte and São Paulo. To this end, causal effects were identified through the estimation of a Bayesian structural time series model. Variations in city vehicle fleets were used from January 2006 to December 2022. In the Belo Horizonte metropolitan area, the results indicate that the variability of the heavy truck fleet was reduced by 30% while that of the light truck fleet increased by 136% in Belo Horizonte. In other municipalities in the metropolitan regions, the variability of the heavy truck fleet reduced by 19% while that of the light truck fleet increased by 147%. In São Paulo, the variability of the heavy truck fleet was reduced by 213% while that of the light truck fleet increased by 72%. In other municipalities in the São Paulo metropolitan area, the variability of the heavy truck fleet was reduced by 63% while that of the light truck fleet increased by 80%. Therefore, it is concluded that the restriction of the freight vehicle had contributed to change the fleet profile of the freight vehicle. Furthermore, the results indicate a potential negative impact on urban mobility, given the significant increase in the number of vehicles in municipal fleets. As decarbonization policies are still in the incipient in Brazil, freight vehicles smaller have not contributed to reducing congestion and pollution, as the increase in the fleet in the areas analyzed was verified.